Estudo do papel da IL-10 endógena e da expressão de pequenos RNAs na modulação da resposta imune durante a infecção pela bactéria intracelular Brucella abortus - Patrícia Paiva Corsetti (2015)
Brucella abortus is a Gram-negative bacterium that causes a chronic disease in humans, cattle and other species called brucellosis. IFN-γ is crucial to control B. abortus infection while IL-10 controls inflammatory response, interfering in bacterium control. In addition, miRNAs can act through post-transcriptional regulation of pro-inflammatory cytokines expression. Encouraged by the interest in analyzing the inflammatory immune response control, the main goal of this thesis is to evaluate the role of endogenous IL-10 and miRNAs during B. abortus infection. IL-10 KO or 129Sv/Ev were infected with B. abortus strain S2308 and the viable bacteria recovered by spleen indicates that IL-10 KO mice were more resistant to this infection revealing completely clearance at 14 weeks post-infection. Furthermore, it was observed increasing production of IFN- γ, TNF-α and IL-17 in serum and spleen supernatant, and IL-12 and TNF-α in BMDCs from IL-10 KO mice. Multifocal granulomes and necrosis were observed in liver tissues from both kind of mice. However, these pathological signs were reduced in IL-10 KO mice. These reduction were accompaniedby increase number of Treg cells and higer expression of TGF-β in spleen cells from IL-10 KO mice. Taken together, the results showed that IL-10 modulates pro-inflammatory response against B. abortus and the absence of this cytokine increase the resistance to this bacterium. To study the role of miRNAs in B. abortus infection, BMDMs from C57BL/6 mice were infected with B. abortus indicating increased expression of IL-12, TNF-α, IL-1β and IL-6. Infected and non-infected BMDMs small RNAs were sequenced. The results showed that about 81% were mapped in miRNA genes. 745 miRNAs were identified in both libraries were 18 miRNAs were diferentially expressed. Sevem miRNAs were validated to be increased expressed while 5 miRNAs were decreased. From those validated miRNAs, mmu-miR-181a- 5p and mmu-miR-99a-5p augmentation were dependent of MyD88. mmu-miR-328-3p showed differences of expression when compared to C57BL/6 in the absence of STING but not in MyD88 KO cells. mmu-miR-21a-5p, mmu-miR-98-5p and mmu-miR-146b-5p decreased expression indicatied the importance of MyD88 to maintain these reduction. However, in STING KO cells these miRNAs were down expressed as in C57BL/6 cells. Among miRNAs diferentially expressed, mmu-miR-181a-5p and mmu-miR-21a-5p were selected to next evaluations. Enrichment in silico analyses of biological pathways of these miRNAs targets identified 19 or 13 biological pathways to mmu-miR-181a-5p and mmu-miR- 21a-5p, repectively. To biological analyses of miRNAs, BMDMs were tranfected with specific mimics or inhibitors resulting in increasing or descreasing of miRNA availability in cells. Gene expression of TNF-α or IL-10 were obtained from BMDMs transfected with mimics or inhibitors after infected with B. abortus sowing the role of mmu-miR-181a-5p or mmu-miR- 21a-5p, repectively, to control the expression of these important cytokines. Until now, the results indicates a miRNA profile diferentially expressed and future evaluations will clarify the role of these miRNAs in immune resposnse regulation during B. abortus infection.